2020
DOI: 10.1080/00365513.2020.1741023
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow- and adipose tissue-derived mesenchymal stem cells from donors with coronary artery disease; growth, yield, gene expression and the effect of oxygen concentration

Abstract: Mesenchymal stem cells (MSCs) for cardiovascular cell therapy are procured from different sources including bone marrow and adipose tissue. Differently located MSCs differ in growth potential, differentiation ability and gene expression when cultured in vitro, and studies show different healing abilities for different MSC subgroups. In this study, bone marrow derived MSCs (BMSCs) and adipose tissue derived MSCs (ADSCs) from six human donors with coronary artery disease were compared for growth potential and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Adipose-derived stem cells produce many molecules responsible for cell signaling, such as cytokines [29,74], growth factors [28,75], morphogens [76], chemokines [27,77], and extracellular vesicles [78][79][80], improving various cellular mechanisms. Interestingly, compared to BM-MSCs-the second most frequently considered MSCs for stem cell therapy-ASCs secrete more growth factors, and this feature increases their regenerative capacity [2,81]. It has also been shown, in vivo, that ASCs are better in the bioactive factors secretion such as nerve growth factor (NGF), hepatocyte growth factor (HGF), monocyte chemotactic protein 1 (MCP-1), colony stimulator of granulocyte-macrophage factor (GM-CSF), granulocyte colony stimulating-factor (CSF), interleukin 1 receptor antagonist (IL-1RA), interleukin (IL)-6 and IL-8 versus bone marrow (BM)-MSCs [27].…”
Section: Adipose-derived Stem Cells Secretomementioning
confidence: 99%
See 1 more Smart Citation
“…Adipose-derived stem cells produce many molecules responsible for cell signaling, such as cytokines [29,74], growth factors [28,75], morphogens [76], chemokines [27,77], and extracellular vesicles [78][79][80], improving various cellular mechanisms. Interestingly, compared to BM-MSCs-the second most frequently considered MSCs for stem cell therapy-ASCs secrete more growth factors, and this feature increases their regenerative capacity [2,81]. It has also been shown, in vivo, that ASCs are better in the bioactive factors secretion such as nerve growth factor (NGF), hepatocyte growth factor (HGF), monocyte chemotactic protein 1 (MCP-1), colony stimulator of granulocyte-macrophage factor (GM-CSF), granulocyte colony stimulating-factor (CSF), interleukin 1 receptor antagonist (IL-1RA), interleukin (IL)-6 and IL-8 versus bone marrow (BM)-MSCs [27].…”
Section: Adipose-derived Stem Cells Secretomementioning
confidence: 99%
“…Adipose-derived stem cells are of great interest in angiogenic therapy as they are good and abundant source of proangiogenic proteins such as FGF-2, HGF, VEGF, PDGF, Ang-1, Ang-2 [33,58]. They secrete a higher concentration of Ang, LIF, and TGF-β1 factors than BM-MSCs and equal levels of VEGF-A and HGF [81]. In 2009, Wei et al showed that concentrated ASC conditioned media can block postischemic p38 activation with concomitant neuroprotective function of IGF-1 and BDNF, thus protecting neurons in vitro and in vivo and preventing loss of hippocampal and cortical volume [140].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Various sources and collection techniques make it easier for ASCs to be obtained because they can adjust to the conditions of each laboratory. Techniques that can be used to obtain ASCs are liposuction and abdominoplasty 9,10,19 . When compared to BMSCs, ASCs have similar characteristics to BMSCs.…”
Section: Adipose-derived Mesenchymal Stem Cells Versus Bone Marrow-dementioning
confidence: 99%
“…Hypoxia (1%) increases the proliferation not only in early passages but also in late passages as compared to normoxic cultures and extends the lifespan of MSCs [61]. Significantly higher number of cells as well as increased viability of ADSC occurs in hypoxic conditions [93]. Rat bone marrow MSC cultured at 5% oxygen levels exhibited increased number of colonies and shorter population doubling time as compared to normoxic cultured cells [94].…”
Section: Effect Of Hypoxia On Proliferative Potential Of Cellsmentioning
confidence: 99%